the Influence of Problem Based Learning and Self Directed Learning Models on Students' Problem Solving Abilities - Lisa Sutami Suharlan; Muhammad Arsyad; Pariabti Palloan (Postgraduate, University of Mataram, 2023)
This research is actual experimental research using a 2x2 factorial design. The aim of this research is to analyze the overall difference in the Problem Solving abilitie of students who are taught using the Problem Based learning model and those taught using the discovery learning model and to analyze the interaction between the learning model and self direct learning on the solving abilities of class XI MIA students. The sample in this study was 48 students consisting of two classes XI MIA 1 as a class taught using the Problem based learning model and class XI MIA 3 as a class taught using the discovery learning model. The average score for problem solving abilities taught using the Problem based learning model was 67.50 and those taught using the discovery learning model was 57.90. The difference in the average score of Problem Polving abilities of students who are taught using the Problem Based learning model and those taught using the discovery learning model for students who have high self-directed learning is 67.30 and 60.20. Meanwhile, the average score for problem solving abilities for self-directed learning students is low at 62.70 and 56.30. The ANOVA test results show that there is no interaction between the learning model and self-directed learning on students' Problem Solving abilitie.